How conformational changes near the F pocket of MHC class I proteins mediate chaperone assisted peptide loading - Göppert, Simone; Springer, Sebastian; Zacharias, Martin (Frontiers in Immunology, 2025)
BackgroundEfficient recognition of antigenic peptides bound to major histocompatibility complex (MHC) class I molecules on the surface of cells by immune cells requires sufficiently stable peptide-MHC I complexes. Antigenic peptides of 8–10 amino acids are typically bound in a narrow cleft between two flanking α1 and α2 helices on top of an extended β sheet floor. For some MHC I alleles the efficient loading with high-affinity peptides in the endoplasmic reticulum (ER) requires the transient binding and assistance of the chaperone proteins tapasin and/or TAPBPR. The structures of both chaperones in complex with MHC I molecules have been resolved and indicate similar structural interface elements and also similar structural changes of the bound MHC I molecules which includes a significant shift of an α2–1 helix, a segment of the α2 helix, which partially opens up the binding cleft.MethodsThe role of this α2–1 helix movement for the peptide loading and editing processes is not fully understood. We employed extensive Molecular Dynamics (MD) simulations and free energy calculations to estimate free energy changes associated with the α2–1 helix movement in the absence as well as presence of low- and high-affinity peptides and in complex with tapasin or TAPBPR.ResultsThe α2–1 helix shift with respect to the conformation in a native MHC I peptide complex significantly destabilizes the binding of peptides and can induce partial dissociation in case of low and medium-affinity peptides. Only a bound high-affinity peptide leads to a narrowing of the binding cleft and reduces the interaction of the MHC I with the chaperone molecules.ConclusionsThe simulations indicate that the conformational shifts of the α2–1 helix with respect to the chaperone and the MHC I molecule play a dominant role for destabilizing peptide binding as well as triggering release from the chaperone in case of high-affinity peptide binding. In addition to the role of the α2–1 helix, we also compared the motion of a loop region found near the N-terminus of tapasin and TAPBPR that may also play a role in the chaperone process.